What sweeter music: an examination of the development and popularity of carol services in cathedrals - Williams, Rowan Clare (Journal of beliefs and values, 2024)
Carol services have always been among the most popular of cathedral offerings, including with those who have little or no regular church affiliation. Their high-quality music may make them attractive to the growing numbers of ‘spiritual but not religious’, in similar ways to choral evensong; the fact that they also tell the story of human salvation through the incarnation creates an opportunity for mission which is often underestimated. The success of carol services might even stimulate questions as to whether nostalgia and tradition, paradoxically, act as drivers for mission in cathedrals. A rethinking of Benedictine identity is key to many cathedrals’ exploration of their place in a post-Covid world of rapid change: the popularity of ‘traditional’ services in a cathedral setting is one indicator of how the search for Benedictine stabilitas might become a positive rather than a backwards-looking movement in a time of uncertainty.